Widefield Swept-Source Optical Coherence Tomography Angiography Assessment of Choroidal Changes in Vogt-Koyanagi-Harada Disease - Qian, Yujing; Yang, Jingyuan; Liang, Anyi; Zhao, Chan; Gao, Fei; Zhang, Meifen (Frontiers in Medicine, 2021)
Purpose: To investigate choroidal changes in patients with Vogt-Koyanagi-Harada disease (VKH) using widefield swept-source optical coherence tomography angiography (SS-OCTA). Methods: In this cross-sectional study, 133 eyes of 69 patients with VKH (52 eyes of 28 active VKH patients and 81 eyes of 41 inactive VKH patients) and 104 eyes of 52 age and sex matched healthy volunteers were imaged using a widefield SS-OCTA instrument. On 12 mm × 12 mm OCTA scans, mean choroidal thickness (MCT), choroidal vascularity index (CVI), choriocapillaris (CC) flow area, and mean retinal thickness (MRT) were separately calculated in the fovea (diameter of 1 mm) and in concentric rings with different radii (1–3, 3–6, 6–9, and 9–12 mm). Results: Eyes with active VKH showed significant increases in MCT, CVI, and MRT, and decreased CC flow area in all central and peripheral regions (0–1, 1–3, 3–6, 6–9, and 9–12 mm) than in the healthy eyes (p ≤ 0.01) and inactive VKH eyes (p < 0.05). Inactive VKH eyes only showed marked decrease in CC flow area in all regions compared with controls (p < 0.05). Flow voids were observed in 51 of 52 (98.1%) active VKH eyes and 50 of 81 (61.7%) inactive VKH eyes on 12 mm × 12 mm OCTA. The MCT of all regions was significantly correlated with age, disease duration, and disease activity, whereas CVI was associated with age and disease activity. The CC flow void was related to visual acuity in all regions (p < 0.05). Conclusion: Widefield SS-OCTA enables a more comprehensive evaluation of chorioretinal changes in patients with VKH disease. Structural and vascular abnormalities are observed in both the central and peripheral choroid and are closely correlated with disease activity.